Trends in Google Docs Application for Collaborative Academic Writing: A Bibliometric Analysis of Research Publications - Sukmojati, Edi; Alifya Rahma, Shafira; Ummah, Hoirul; Putra, Rendi Dwi; Attabik, Muhammad Haikal (Journal of Language and Literature Studies, 2025)
Using Google Docs for collaborative writing has grown more important in many locations worldwide. Prior studies have demonstrated that classroom collaboration obstacles stem from team members having disparate proficiency levels with the required platform and challenges faced while implementing collective tasks. This study gathered data from the Scopus database to evaluate the scientific outcomes of articles about using Google Docs in collaborative writing. Scopus indexed a collection of data, A total of 173 selected publications have been collected during the inclusion phase, covering the last decade from 2012 to 2024. Starting at 10 publications in 2012, the number fluctuated slightly in the early years, reaching a low point of 5 in 2015. After 2016, the trend consistently increased, with notable growth after 2018. The publications rose sharply from 14 in 2019 to 25 in 2022, followed by a slight dip to 17 in 2023. In 2024, the number rebounded to 24 publications. Data sources in the form of conferences accounted for 29.49% and journal publications with a total of 70.51%. Overall, the data indicates growing research interest and academic engagement with Google Docs in collaborative writing over time, particularly in recent years. The quantitative study findings reveal a substantial rise in study results on using Google Docs in the United States over the last five years. A descriptive Scopus database and bibliometric review were conducted to find publishing patterns related to Google Docs in collaborative academic research. The entire average number of citations that have been published is calculated using Microsoft Excel technology. The trend of research collaboration utilizing Google Docs for collaborative writing is somewhat restricted, and the study subjects are significantly diverse. This study has several limitations, mainly that data were only selected and filtered from the Scopus database, making our analysis reliant purely on the reliability of the provided input source.